The Possibility of Utilizing Imported Frozen Bull Semen in the Libyan Arab Republic (L.A.R.) - DARWASH, ADNAN O. (The Libyan Journal of Agriculture, 2023)
A survey of cattle population, breeds and distribution in the Libyan Arab Republic was made. Future plans for cattle development were studied. It was found that artificial insemination, using locally processed or imported frozen semen, could be introduced. Frozen semen ampules of Friesian bulls were purchased from abroad, stored in liquid nitrogen and utilized successfully. The cost of one ampule of frozen semen arriving in Tripoli ranged from 2.27-2.75 L.D. while it was 5.31 L.D. for that of a natural service. This difference would be greater if the genetic superiority and the saving in valuable man hours and feedstuff were considered. It was suggested that imported frozen semen could be an asset to cattle development plans or to supplement future artificial insemination service.